Community-acquired infection with hypervirulent Clostridium difficile isolates that carry different toxin and antibiotic resistance loci: A case report (2017)
Background: Clostridium difficile infection (CDI) leads to the onset of antibiotic-associated diarrhea (AAD) and a wide range of gastrointestinal pathologies. Currently, CDI is one of the most important opportunistic infections at the intrahospital level and an exponential increase in community-acquired infections has been reported. Herein, we evaluated the relationships (at phylogenetic and genetic population structure levels), as well as the molecular toxigenic and antibiotic resistance profiles of a set of isolates established from a case of community acquired-CDI. Case presentation: A 30-year-old woman with no history of hospitalization who was exposed to antibiotics (ampicillin/sulbactam and metronidazole) after a cat-bite wound was presented. The patient had a continuous episode of diarrhea; a stool sample was then collected and community acquired-CDI was confirmed by molecular tests and in vitro culture. Seven isolates were established and subsequently subjected to: (i) Multilocus sequence typing, all isolates belonging to ST-1 (associated with hypervirulent strain (027/BI/NAP1); (ii) description of their toxigenic profile: two of the isolates (Gcol.49 and Gcol.91) were positive for the genes coding for the major toxins (tcdA and tcdB) and their negative regulator (tcdC). All isolates were positive for the cdtB gene encoding one of the binary toxin subunits, while only two (Gcol.51 and Gcol.52) were positive for cdtA; and (iii) identification of antibiotic resistance molecular markers, where there was no difference in gyrA or gyrB gene polymorphisms (related to quinolone resistance), but rather at loci presence/absence, being just one isolate negative, whereas the others showed a differential presence of the tet, ermB and Tn916 regions. The former was associated with resistance to tetracycline and the other two for erythromycin/clindamycin. Conclusions: This case represents the first report of community acquired-CDI in Colombia associated with hypervirulent strains and shows that isolates obtained from a single patient can carry different toxin and antibiotic resistance loci. © 2017 The Author(s).